NATURE AND GEOGRAPHY IN THE COLOMBIAN TERRITORIAL FORMATION - Vargas, Gloria Maria (Revista do Departamento de Geografia, 2011)
The notions on nature had an important influence on the territorial consolidation of the early Colombian State during the XIX century. Different notions of nature, with its cartographic representations and material practices, were part of the social construction of the territory and gave legitimacy to power structures that impacted the whole process. These notions and material practices can also be seen as part of the colonial geopolitical project that permeated the “intelligentsia criolla”, which incorporated some of its postulates selectively for its own power project. Some of these postulates are framed in a dualistic and excluding logic based on deterministic notions of nature and geography, and built nature-society equations that instead of unifying the territory as a step in the nation building, fomented a segregated spatial pattern that persists until today.